Automatic Three-Dimensional Magnetic Resonance-based measurements of tumour prominence and basal diameter for treatment planning of uveal melanoma. (October 2022) - Klaassen, Lisa; Jaarsma-Coes, Myriam G.; Verbist, Berit M.; Vu, T.H. Khanh; Marinkovic, Marina; Rasch, Coen R.N.; Luyten, Gregorius P.M.; Beenakker, Jan-Willem M.
Highlights: Three-dimensional definitions of eye tumour thickness and diameters were composed. In general, these measurements agreed with conventional two-dimensional ultrasound. Magnetic resonance imaging was more accurate when tumours were not completely visible on ultrasound. Automatic measurements on contrast-enhanced T1-weighted images are preferred. Abstract: Background and Purpose: Three-dimensional (3D) Magnetic Resonance Imaging (MRI) is increasingly used to complement conventional two-dimensional ultrasound in the assessment of tumour dimension measurement of uveal melanoma. However, the lack of definitions of the 3D measurements of these tumour dimensions hinders further adaptation of MRI in ocular radiotherapy planning. In this study, we composed 3D MR-based definitions of tumour prominence and basal diameter and compared them to conventional ultrasound. Materials and methods: Tumours were delineated on 3DT2 and contrast-enhanced 3DT1 (T1gd) MRI for 25 patients. 3D definitions of tumour prominence and diameter were composed and evaluated automatically on the T1gd and T2 contours. Automatic T1gd measurements were compared to manual MRI measurements, to automatic T2 measurements and to manual ultrasound measurements. Results: Prominence measurements were similar for all modalities (median absolute difference 0.3 mm). Automatic T1gd diameter measurements were generally larger than manual MRI, automatic T2 and manual ultrasound measurements (median absolute differences of 0.5, 1.6 and 1.1 mm respectively), mainly due to difficulty defining the axis of the largest diameter. Largest differences between ultrasound and MRI for both prominence and diameter were found in anteriorly located tumours (up to 1.6 and 4.5 mm respectively), for which the tumour extent could not entirely be visualized with ultrasound. Conclusions: The proposed 3D definitions for tumour prominence and diameter agreed well with ultrasound measurements for tumours for which the extent was visible on ultrasound. 3D MRI measurements generally provided larger diameter measurements than ultrasound. In anteriorly located tumours, the MRI measurements were considered more accurate than conventional ultrasound.